2012
DOI: 10.1159/000341547
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Maoto in an Influenza Season Where Reduced Effectiveness of Oseltamivir Was Observed – a Clinical, Non-Randomized Study in Children

Abstract: Background: In an influenza season where reduced effectiveness of oseltamivir was observed, we investigated the effectiveness of Maoto for influenza infection in children. Methods: Patients diagnosed with influenza by rapid diagnostic kit underwent treatment in one of the following groups: Maoto-treated group (group 1 (M)); oseltamivir-treated group (group 2 (O)); Maoto+oseltamivir-treated group (group 3 (M+O)); zanamivir-treated group (group 4 (Z)); and Maoto+zanamivir-treated group (group 5 (M+Z)). Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…It has been reported that maoto had a better reducing effect for the duration of fever in children infected with type A influenza [2, 3]. It has also been reported that the duration of fever in maoto-treated group was shortened significantly rather than in oseltamivir-treated group in adult patients with influenza [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that maoto had a better reducing effect for the duration of fever in children infected with type A influenza [2, 3]. It has also been reported that the duration of fever in maoto-treated group was shortened significantly rather than in oseltamivir-treated group in adult patients with influenza [4].…”
Section: Discussionmentioning
confidence: 99%
“…Maoto has been used for the treatment of febrile disease, such as influenza-like illness (high fever, headache, pain, and cough) since ancient times, and has been used frequently for a treatment of early phase of recent influenza virus infections in Japan. Recently, maoto has been reported to have antipyretic effect in pediatric patients [2, 3] and adult patients with type A influenza virus infection [4]. However, the anti-influenza virus activity of maoto has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported that MHT has antipyretic effect in pediatric patients [8]. Other studies showed that MHT has antiasthmatic effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment increases antiinfluenza virus IgM, IgA, and IgG1 antibody titers in nasal fluid, bronchoalveolar lavage fluid, and serum, respectively, showing effects similar to those of shoseiryuto. Clinical and randomized studies have also claimed that maoto may be effective in cases of influenza with low sensitivity to oseltamivir and younger patients under 5 years of age (Kubo and Nishimura, 2007;Toriumi et al, 2012).…”
Section: Maotomentioning
confidence: 99%